Awareness of nurses regarding HIV/AIDS - Jan, Abida (Indian Journal of Nursing Sciences, 2024)
Background: Human immuno virus is one of the drastic infectious that causes deterioration of health condition. This causes total breakdown of the body systems particularly the immune system. The knowledge regarding AIDS in health care staff is very much essential as they remain in close contact with patients suffering from these deadly infections or disease. The health care professionals particularly the nurses should know the causes, pathophysiology, signs and symptoms, prevention and management of this deadly disease. In order to know that how much knowledge our nurses have in the tertiary care hospital of Kashmir, this mini-research study was carried out in emergency medicine and other departments of SKIMS, soura and the results so obtained are mentioned in this report. Aim: The aim of this study was to assess the knowledge of nurses in a tertiary care hospital regarding HIV/ AIDS. Material and methods: A descriptive cross sectional study was conducted over a Brief period at tertiary care hospital in Srinagar amongst nursing staff of the Hospital. The data was collected by using a validated, modified structured questionnaire earlier used by Atul et al. Results: The results of the study depicted that 45% of staff had an adequate knowledge regarding the topic while as maximum numbers of participants i.e. 55 % had high knowledge regarding HIV/AIDS and thus were highly aware. There was no participant having 0% of knowledge level. Conclusion: This can be concluded that the Nursing Officers were fully aware of the disease under study particularly the causes, modes of transmission, prevention and management of HIV/AIDS.